Analisis Preferensi Konsumen Bunga Krisan Potong (Chrysanthemum morifolium) Di Jawa Timur - Tina Arum Afiati; Koesriwulandari Koesriwulandari; Erna Haryanti Koestedjo (Study Program of Agribusiness, Faculty of Agriculture, University of Wijaya Kusuma Surabay, 2022)
This study aims to analyze the attributes of cut chrysanthemums that have a relationship with the consumption of cut chrysanthemums in East Java, analyze the attributes of cut chrysanthemums that are preferred and most considered in East Java and analyze consumer attitudes towards the attributes of cut chrysanthemums in East Java. The research location was determined deliberately, namely in East Java which is a consumptive area for cut flowers. Respondents were determined by the Solvin Formula, namely 100 respondents. The analytical method used is the chi-square analysis method and fishbein multi-attribute analysis. The results showed that: Attributes that were significantly related to the consumption of cut chrysanthemum flowers were type attributes, consumer preferences in East Java were spray cut chrysanthemum flowers, white in color, and in the shape of a pompom. The attribute of cut chrysanthemums that is most considered in purchasing decisions is the color attribute. The most considered to the less considered attributes are color, shape, and type. Consumer attitudes towards the attributes of shape, type, and color of cut chrysanthemum flowers are positive.Keywords: Chrysanthemum Flower, Chi-Square Analysis, Consumer Preference, Fishbein Multiattribute Analysis